ANALISIS KONVERGENSI ANTAR PROVINSI (STUDI KASUS PULAU SUMATERA) - Arief Budiman; Hasdi Aimon; Yeniwati Yeniwati (Jurnal Ecogen, 2018)
This  study aims to determine an analyze the influence of foreign direct investment, transfer payment and human development affect capita income. These three variables also used to determine convergence that happenened on the island of Sumatera. Data used from 2012 to 2017involve 10 provinces on the island of Sumatera. This data on this research is secondary data published by the Central Bureau of Statistic. The analytical method used is regression panel to estimate impact dependent variables on capita income. To determine sigma convergence use standart deviation lag of Gross Regional Domestic Income per capita. And to determine beta convergence use Generalized Method Momment (GMM). The result of this study show foreign direct investment, transfer payment and human development have significant impact on per capita income. The result of sigma convergence show the island of Sumatera have sigma convergence from 2012 to 2017. The resut of beta convergence show the island of Sumatera have beta convergence and reach half live convergence in 12 years. Keywords : Convergence, foreign direct investment, transfer payment, human development